L’effondrement de la représentation et la crise politique argentine - Silvia Robin (Cahiers des Amériques Latines, 2002)
The political crisis of 2001 signals the structural weakness of public representation in Argentina marked by an exacerbated presidentialism, deformed federalism and an artificial bi-partyism. The strengths and weaknesses of the alliance taken to power in 1999 demonstrate voter’s desire for change, their sensibility to mediatised messages as well as the difficulties in governing encountered by a heterogeneous coalition. Their failure marked to another degree the weakening of the state and the discredit of politics which repeats the formula «That they all leave».